PENGARUH KOMITMEN ORGANISASIONAL DAN KEPUASAN PELATIHAN TERHADAP INTENTION TO STAY MELALUI KEPUASAN KERJA - Sitanggang, Maylisa Rianti; Azzuhri, Misbahuddin (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the effects of organizational commitment and training satisfaction on the intention to stay in Novo Club with job satisfaction as the mediating variable. This research is categorized as an explanatory study as it explains the causal relationship between variables through hypothesis testing. The respondents are 83 members of the first batch of Novo Club. In order to identify both direct and indirect effects, path analysis was incorporated. This study finds that organizational commitment and job satisfaction significantly influence the intention to stay and that training satisfaction has no significant effect on the said intention. Furthermore, organizational commitment indirectly affects the intention to stay through job satisfaction, and training satisfaction also indirectly influences the intention to stay through job satisfaction.